Genetic analysis of the adenovirus E4 6/7 trans activator: interaction with E2F and induction of a stable DNA-protein complex are critical for activity. - Neill, S D (1991)
The adenovirus early E4 transcription unit encodes a 19-kDa polypeptide that trans activates transcription of the early E2 gene and is dependent on the binding sites for the E2F transcription factor. Biochemical assays have shown that the E4 protein, a product of the 6/7 open reading frame, interacts with the E2F transcription factor and alters its DNA binding characteristics, resulting in the formation of a very stable DNA-protein complex. We have generated a series of E4 mutants to determine the requirements for the interaction with E2F and the induction of a stable E2F complex on the E2 promoter in relation to the trans activation of E2 transcription. We find that the trans-activation function of E4 is dependent on the ability of the protein to interact with E2F and that full trans activation is dependent on the induction of the E2F stable complex. Interestingly, several mutants distinguish these events, since they retain the ability to interact with E2F but have lost the capacity to induce the stable complex. Since these mutants can still trans activate, albeit at reduced levels, these results suggest that the E4 protein contributes to trans activation that is independent of stable complex formation.